The Effect of Zeolite/Chitosan Hybrid Matrix for Thermal-stabilization Enhancement on the Immobilization of Aspergillus fumigatus α-Amylase - Yandri Yandri; Hendri Ropingi; Tati Suhartati; John Hendri; Bambang Irawan; Sutopo Hadi (Ital Publication, 2022)
In this paper, the A. fumigatus α-amylase had been immobilized onto zeolite/chitosan hybrid to improve its thermal-stabilization for industrial needs. The methods applied enzyme production, isolation, partial purification, immobilization, and characterization. The optimum temperatures of the native and immobilized enzymes were 50 and 55˚C, respectively. The native enzyme has KM of 3.478 ± 0.271 mg mL-1 substrate and Vmax of 2.211± 0.096 µmole mL-1 min-1, while the immobilized enzyme has KM value of 12.051 ± 4.949 mg mL-1 substrate and Vmax of 1.602 ± 0.576 µmole mL-1 min-1. The residual activity of the immobilized enzyme retained up 10.97% after fifth reuse cycles. The native enzyme has ΔGi of 104.35 ± 1.09 kJ mole-1 and t½ of 38.75 ± 1.53 min, while the immobilized enzyme has ΔGi of 108.03 ± 0.05 kJ mole-1 and t½ of 180.03 ± 3.31 min. According to the increase in half-life (t½), stability improvement of the A. fumigatusα-amylase was 4.65 times greater than the native enzyme. Thus, the zeolite/chitosan hybrid is used as a new supporting matrix for further enzyme immobilization to stabilize the enzymes. Doi: 10.28991/ESJ-2022-06-03-06 Full Text: PDF